Positive psychological interventions for people with epilepsy: An assessment on factors related to intervention participation - Lai, Siew Tim; Lim, Kheng Seang; Tang, Venus; Low, Wah Yun (Elsevier, 2018)
Background: Positive psychological interventions (PPI) are increasingly employed as a coping strategy with physical and mental conditions, including neurological diseases. Its effectiveness on improving wellbeing in people with epilepsy (PWE) has been shown in a few studies. This study aimed to explore factors related to participants' willingness to engage in psychological interventions from the perspective of patients with epilepsy. Methods: Participants answered a needs assessment questionnaire eliciting information about their illness perception (Brief Illness Perception Questionnaire (Brief-IPQ)), emotions (Hospital Anxiety and Depression Scale (HADS)), willingness to participate in psychological interventions, preferences in types of PPI and intervention designs, as well as barriers in seeking mental health services. Results: A total of 154 patients with epilepsy participated, with a mean age of 37.3 years (range 16–86 years). Most patients had focal epilepsy (68.2%), and drug-resistant (59.1%). Majority (71.4%) of them indicated a strong willingness to participate in PPI. Out of nine types of PPI, character strengths, mindfulness-based and expressive-based interventions were highly preferred. Those with negative illness perception (p = 0.001), anxiety (p = 0.004), and being unemployed (p = 0.048) were more willing to participate in PPI. Most participants preferred group rather than individual session, and a shorter duration (30 min) was favored by most. Conclusion: This study captured the self-report willingness to participate in psychological interventions. Findings suggested that psychological interventions delivered in short-group session were highly preferred. Future study is required to determine the feasibility of such design for patients with epilepsy.